New taxa and some clarification of the tribe Steirodontini (Orthoptera: Tettigoniidae; Phaneropterinae): Tenth contribution to the suprageneric organization of Neotropical phaneropterines - Cadena-Castañeda, Oscar J. (Zootaxa, 2016)
The tribe of the giant katydids Steirodontini is reviewed, its relationship with other groups of Phaneropterinae from the Old and New World is discussed, and an updated key to genera is presented. Nicklephyllum n. gen. is established to accommodate one species described as Stilpnochlora acanthonotum Nickle, 1985 from Colombia. Cnemidophyllum tani n. sp. from the Colombian Amazon is described. Another new combination and two synonymies are proposed: Steirodon (Frontinus) emsleyi (Piza, 1979) n. comb., Steirodon (Posidippus) parastahli Piza, 1979 n. syn. (of Steirodon (Steirodon) ponderosum Stål, 1873), and Steirodon (Posidippus) tricenarius (Piza, 1974) n. syn. (of Steirodon (Frontinus) rufolineatum Emsley, 1970). Finally, Steirodon (Posidippus) rarospinulosum (Brunner von Wattenwyl, 1891), only known from Peru, is reported from the Colombian Amazon.